Overview Of The Implementation Of Hazard Identification Risk Assessment And Determining Control (HIRADC) In Girder Lifting Work at PT Wijaya Karya Gedung Gedung Tbk . Halim High Speed Train Station Construction Project - madhona, yenny frisca; Syah SP, Agni; Pramesti Hadiyani, Fadilah (LPPM Institut Teknologi Petroleum Balongan, 2024)
Infrastructure development at PT. Wijaya Karya Gedung Gedung Tbk The Halim High Speed ​​Train Station Construction Project certainly involves a lot of human resources and a variety of equipment. However, this construction activity can cause undesirable impacts, including aspects of work safety and the environment. Therefore, construction activities must pay attention to applicable Occupational Health and Safety (OHS) standards and provisions. There are several high-risk lifting jobs on the Halim Fast Train Station Construction Project, one of which is lifting girders. The aim of this research is to find out an overview of the application of Hazard Identification Risk Assessment and Determining Control (HIRADC) in girder lifting work at PT Wijaya Karya Gedung Gedung, Tbk. The Halim High Speed ​​Train Station Construction Project is in accordance with PUPR Ministerial Regulation No.10 of 2021. Data processing carried out in this reasearch used qualitative methods with secondary data collection. The company has a HIRADC program, namely hazard identification, risk assessment and risk control. The making of the HIRADC itself is carried out by paying attention to the sequence of work stages contained in the IK (Work Instructions) with Doc No.: WIKA-BG-PDSMM-IK-44 and Ref: 0440/DIR/KCIC/04.19 so that the HIRADC maker can assess potential hazards from each stage of work activities. and has implemented hazard identification, risk assessment, and risk control in girder lifting work. Programs, procedures and implementation are in accordance with PUPR regulation no. 10 of 2021 concerning Construction Safety Management Systems (SMKK).